2011
DOI: 10.2147/opth.s19469
|View full text |Cite
|
Sign up to set email alerts
|

The effect of topical 0.05% cyclosporine on recurrence following pterygium surgery

Abstract: Purpose:To investigate the role of postoperative topical 0.05% cyclosporine A (CsA) eye drops (Restasis®, Allergan Pharmaceutical) in the prevention of recurrence among patients with primary pterygium treated with bare-sclera technique.Methods:In this prospective randomized controlled study, 36 eyes (34 patients) with primary pterygium were randomized into two groups: Group I comprised 18 eyes (18 patients), and Group II comprised 18 eyes (16 patients). Bare sclera technique was performed in both groups. In Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 26 publications
(28 reference statements)
0
21
0
6
Order By: Relevance
“…Bahar et al [18] showed that the use of fibrin glue was associated with a significantly shorter operative time and greater patient acceptance compared with using sutures. We observed [19]. Tok et al used cyclosporine following primary excision in primary pterygium cases, and observed the recurrence of 12.9% [13], Aydin et al who used topical cyclosporine with conjunctival limbal autograft observed a recurrence of 3.4% [20] and Ozulken K et al observed a recurrence of 7.7% with cyclosporine [21].…”
Section: Discussionmentioning
confidence: 62%
“…Bahar et al [18] showed that the use of fibrin glue was associated with a significantly shorter operative time and greater patient acceptance compared with using sutures. We observed [19]. Tok et al used cyclosporine following primary excision in primary pterygium cases, and observed the recurrence of 12.9% [13], Aydin et al who used topical cyclosporine with conjunctival limbal autograft observed a recurrence of 3.4% [20] and Ozulken K et al observed a recurrence of 7.7% with cyclosporine [21].…”
Section: Discussionmentioning
confidence: 62%
“…The authors postulated that artificial tears could help decrease inflammation in the early postoperative period by improving tear film function. In addition, postoperative application of cyclosporine is associated with lower rates of recurrences and complications following pterygium excision [27,28]. Of note, preoperative dry eye was found to be the most important prognostic parameter for conjunctival limbal graft survival in a series of 31 patients with total limbal stem-cell deficiency [29].…”
Section: Discussionmentioning
confidence: 99%
“…CsA, an anti-inflammatory agent, has been administered topically to treat a variety of inflammatory disorders of the ocular surface [60]. Postoperative application of topical 0.05% CsA can provide effective prevention of recurrence after primary pterygium surgery [64, 65, 95]. To the best of our knowledge, no previous studies have examined the relationship between MMP-3 and MMP-13 expression by pterygium explants and cultured pterygium-derived fibroblasts, and treatment using bevacizumab and/or CsA.…”
Section: Discussionmentioning
confidence: 99%